KRITIK AL-QURÁN TERHADAP BUDAYA KONSUMERISME MASYARAKAT MODERN - putri krisdiana (MUSLIMPRENEUR : Jurnal Ekonomi dan Kajian Keislaman, 2022)
This paper describes the criticism of the Koran against the consumerism culture that develops in modern society. This study examines the main problem of how the Qur'an has a dialectic with this postmodern culture. The author uses this type of literature study by utilizing several books, journals and other scientific works as the main material in this research. After carrying out a series of processes, the author finds that the consumerism culture of modern society is criticized by the Qur'an in several ways: first, forcing oneself to buy an item. This often results in conflicts between individuals and even between families and this is what has been criticized by Q.S. Al-Maidah verse 88. Second, follow a life style excessively. This was criticized by Q.S. Al-A'raf 31. Third, buying liquor. We can observe this trend in today's young people who take drunkenness as a sign that they are not out of date. This culture is also criticized by the Qur'an Surah Al-Baqarah verse 219. Fourth, following the trend and wasteful consumption. This culture has also received criticism from the Qur'an, Surah Al-Isra' verse 29. Fifth, showing off expensive goods. From all the data, we find that the culture of consumerism often leads to showing off expensive goods. This attitude of showing off has been criticized by the Qur'an, Surah Q.S. Al-Isra' verse 37.